Long survival after excision of a primary malignant melanoma of the oesophagus. Issue 5 (May 1991) - Hamdy, F C; Smith, J H; Kennedy, A; Thorpe, J A
Abstract : A woman who had a large primary malignant melanoma of the oesophagus, with evidence of submucosal invasion and several local metastases, underwent resection two years after the onset of retrosternal pain and has survived for 12 years with no recurrence.